The electrochemical reduction of hydrogen sulfide on platinum in several room temperature ionic liquids - O'Mahony, A; Silvester, D; Aldous, L; Hardacre, C; Compton, R (2008)
The electrochemical reduction of 1 atm hydrogen sulfide gas (H 2S) has been studied at a platinum microelectrode (10 μm diameter) in five room temperature ionic liquids (RTILs): [C2mim] [NTf 2], [C4mpyrr][NTf2], [C4mim][OTf], [C4mim][NO3], and [C4mim][PF6] (where [Cnmim]+ = 1-alkyl-3-methylimidazolium, [NTf 2]- = bis(trifluoromethylsulfonyl)imide, [C 4mpyrr]+ = N-butyl- N-methylpyrrolidinium, [OTf] - = trifluoromethlysulfonate, [NO3]- =nitrate, and [PF6]- = hexafluorophosphate). In all five RTILs, a chemically irreversible reduction peak was observed on the reductive sweep, followed by one or two oxidative peaks on the reverse scan. The oxidation peaks were assigned to the oxidation of SH- and adsorbed hydrogen. In addition, a small reductive peak was observed prior to the large wave in [C 2mim] [NTf2] only, which may be due to the reduction of a sulfur impurity in the gas. Potential-step chronoamperometry was carried out on the reduction peak of H2S, revealing diffusion coefficients of 3.2, 4.6, 2.4, 2.7, and 3.1 × 10-10 m2 s-1 and solubilities of 529, 236, 537, 438, and 230 mM in [C2mim][NTf 2], [C4mpyrr][NTf2], [C4mim][OTf], [C4mim][NO3], and [C4mim][PF6], respectively. The solubilities of H2S in RTILs are much higher than those reported in conventional molecular solvents, suggesting that RTILs may be very favorable gas sensing media for H2S detection. © 2008 American Chemical Society.